IDENTIFICAÇÃO DE TOXICIDADE DE NANOPARTÍCULAS DE DIÓXIDO DE TITÂNIO A PARTIR DA ANÁLISE DA EXPRESSÃO GÊNICA E VIAS BIOLÓGICAS BASEADAS NA ATIVIDADE E DIVERSIDADE GÊNICAS RELATIVAS IN SILICO - Anjos, Josiane Fontoura dos (2022)
Due to increased knowledge about the human genome, gene expression techniques are increasingly applied and studied. In bioinformatics and nanotechnology, there is a need for a deeper understanding of toxicology. Therefore, the present work investigates the biological effects on the toxicity of metallic nanoparticles (NPs), such as TiO2, in human cell cultures (co-culture of Caco-2/HT29-MTX, SAE, and THP-1 cells) to identify the differentially expressed genes and significant biological pathways, in sílico, based on safety and pharmacological efficacy of nanoparticle aplication. In this way, a systematic mapping was carried out to seek the necessary resources. Due to the Geo Datasets database availability, three studies with three different human cell lines submitted to TiO2 NPs were listed. The data were prepared and standardized for the execution of the LIMMA package (Bioconductor), and the results of the most and least expressed genes were manually compared in Reactome. The ADAM (Bioconductor) package was executed according to the selected metabolic pathways (Cellular Responses to External Stimuli, Cytokine Signaling in Immune System, and Programmed Cell Death) for each study, and its pathways and subpathways were generated. Each study has its cell line subjected to 10 and 100 μg/mL of TiO2 NPs for 1 and 24h (samples). The samples related to higher concentrations and more extended time obtained more specific reactions involving pathways: cellular response to metallic NPs (external stimulus), induction of pro-inflammatory processes, and evolution of apoptosis process and cell death in the co-culture of Caco-2/HT29-MTX. Due to their origins, the tumor lines showed reactions, suggesting the effectiveness of NP. However, despite the signaling of the inflammatory process of SAE cells (healthy cell), no pathway related to the programming of cell death was identified, indicating the safety of the submitted NP to specific concentrations and exposure times. This doctoral work’s originality lies in the applying tumor and healthy strains at different concentrations and exposure times to NPs, using the studied techniques (LIMMA+ADAM).